2012
DOI: 10.1371/journal.pone.0050369
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Nucleotide Diversity and Evolution of the H Genome in Polyploid Hordeum and Elymus Species Based on the Single Copy of Nuclear Gene DMC1

Abstract: Numerous hybrid and polypoid species are found within the Triticeae. It has been suggested that the H subgenome of allopolyploid Elymus (wheatgrass) species originated from diploid Hordeum (barley) species, but the role of hybridization between polyploid Elymus and Hordeum has not been studied. It is not clear whether gene flow across polyploid Hordeum and Elymus species has occurred following polyploid speciation. Answering these questions will provide new insights into the formation of these polyploid specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Genetic diversity analysis in different genomic combinations will facilitate the understanding of the evolution process and genetic differentiation among different species. The phylogenetic relationships of the StH , StY and StHY genome Elymus species have been reported by using molecular sequences [9, 10, 12, 17–19]. In this study, we used newly developed EST-SSR markers to analyze the phylogenetic relationships of 17 StH , StY and StHY genome Elymus species collected from diverse geographical regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic diversity analysis in different genomic combinations will facilitate the understanding of the evolution process and genetic differentiation among different species. The phylogenetic relationships of the StH , StY and StHY genome Elymus species have been reported by using molecular sequences [9, 10, 12, 17–19]. In this study, we used newly developed EST-SSR markers to analyze the phylogenetic relationships of 17 StH , StY and StHY genome Elymus species collected from diverse geographical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Information on molecular phylogeny and genetic structure among different Elymus species is limited, but necessary for germplasm collection, conservation and utilization. The phylogenetic relationships and genetic components among different Elymus species are largely unknown because of the limited detection ability of specific or unique nuclear gene sequences [9, 10, 12, 17–19]. Genetic diversity analysis among phylogenetically related species is based on the development of transferable and orthologous molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular evolution of DMC1 in Leymus and its potential diploid genome donor species Analysis of the levels of diversity at homoeologous loci in polyploids compared to their diploid relatives may provide insight into how the evolutionary process differs between lineages and between homoeologous loci within lineages (Soltis et al, 2003;Fan et al, 2009Fan et al, , 2012Sun & Sun, 2012). Several studies suggested that genetic diversity in polyploids is often similar to or higher than their diploid progenitors (Otto & Whitton, 2000;Sun et al, 2007;Fan et al, 2009;Sun & Sun, 2012;Wang et al, 2012). However, comparisons of nucleotide diversity showed that the Gss locus on the D genome of hexaploid wheat is lower than that of diploid D genome donor Aegilops tauschii Coss.…”
Section: Phylogenetic Relationships In Leymus Speciesmentioning
confidence: 99%
“…Recent studies have shown that transposable element indels shaped the homoeologous loci, which was responsible for the patterns of diversity of duplicated genes (Sun et al, ; Fan et al, ). It was considered that the levels and patterns of genetic diversity in polyploid populations of independent origins varied depending on the amount of genetic variation initially contributed by the diploid progenitors (Fan et al, , ; Sun & Sun, ). Therefore, differences in the levels and patterns of nucleotide diversity of duplicate genes may reflect numerous influencing forces.…”
mentioning
confidence: 99%
See 1 more Smart Citation